2018
DOI: 10.31661/jbpe.v0i0.912
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Fields of Mobile Phone Jammer Exposure on Blood Factors in Rats

Abstract: Background: The increasing demand for using mobile phones has led to increasing mobile phone jammers as well. On the other hand, reports show that exposure to electromagnetic field causes an increase in the incidence of diseases such as leukemia, cancer, depression and failure in pregnancy outcomes; therefore, the aim of this study is to investigate the effects of exposure to electromagnetic fields of mobile phone jammers on blood factors.Materials and Methods: Thirty male Wistar immature and thirty mature rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a military environment, this ability is essential to interrupt enemy communications. A characteristic aspect is the signal power because, for being effective, the jammer power signal must be equal or higher than the signal power at the receiver, at least one order of magnitude [ 49 ], so that the two signals can collide and cancel each other [ 50 ]. Another equally important application of jammers, also called electronic counter measures (ECM) [ 51 ] is the interruption of enemy radar surveillance by several specific jamming techniques through which the enemy loses the ability to detect, track and visualize objects belonging to the own and friendly forces.…”
Section: Resultsmentioning
confidence: 99%
“…In a military environment, this ability is essential to interrupt enemy communications. A characteristic aspect is the signal power because, for being effective, the jammer power signal must be equal or higher than the signal power at the receiver, at least one order of magnitude [ 49 ], so that the two signals can collide and cancel each other [ 50 ]. Another equally important application of jammers, also called electronic counter measures (ECM) [ 51 ] is the interruption of enemy radar surveillance by several specific jamming techniques through which the enemy loses the ability to detect, track and visualize objects belonging to the own and friendly forces.…”
Section: Resultsmentioning
confidence: 99%
“…high dose and long duration intake may also reveal liver toxicity, especially in athletes. It is worth nothing that reproductive system and sperm/oocyte health are highly sensitive to toxicity (Shojaeifard et al, 2016;. Studies have shown that TT contains steroids, saponins, flavonoids, protodioscins, quercetin, alkaloids, unsaturated fatty acids, vitamins, tannins, resins, nitrate potassium, aspartic acid, and glutamic acid (Akram et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example Kaur and Khera [35] studied the impact of cell phone radiations on pituitary gland and biochemical parameters in albino rat. Special focus was also carried out on the effect of mobile phone radiation on spermatogenesis [36], testicular function [37], brain structure and functions [38], thyroid glands [39], heart tumors [40], anxiety level [41] and on blood factors [42]. In addition, Wyde et al [43] studied the effects of cell phone radiation on body temperature in rodents.…”
Section: Introductionmentioning
confidence: 99%